2015
DOI: 10.1001/jamaophthalmol.2015.2249
|View full text |Cite
|
Sign up to set email alerts
|

Association of Systemic Lupus Erythematosus With Uveitis

Abstract: ystemic lupus erythematosus is a systemic autoimmune condition that can be associated with uveitis. The prevalence of SLE as a cause of uveitis varies in the literature. In 1990, Rosenbaum and Wernick 1 reported on the use of routine antinuclear antibody (ANA) testing for patients with uveitis. Their Bayesian analysis required a pretest probability of SLE in patients with uveitis. Rosenbaum and Wernick 1 estimated a prevalence of SLE as a cause of uveitis as 0.1%. This estimate was based on 1218 patients in 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…The major pathological changes in lupus retinopathy are attributed to vasculopathy rather than a true vasculitis, characterized most commonly by an immune complex-mediated microangiopathy [7]. Retinopathy in SLE is suggestive of elevated disease activity and correlates with central nervous system and kidney involvement during the course of SLE, and is a marker of poor prognosis for survival [6-9]. It may also indicate inadequate control of systemic disease [9, 10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major pathological changes in lupus retinopathy are attributed to vasculopathy rather than a true vasculitis, characterized most commonly by an immune complex-mediated microangiopathy [7]. Retinopathy in SLE is suggestive of elevated disease activity and correlates with central nervous system and kidney involvement during the course of SLE, and is a marker of poor prognosis for survival [6-9]. It may also indicate inadequate control of systemic disease [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Retinopathy in SLE is suggestive of elevated disease activity and correlates with central nervous system and kidney involvement during the course of SLE, and is a marker of poor prognosis for survival [6-9]. It may also indicate inadequate control of systemic disease [9, 10]. Treatment strategies for SLE include hydroxychloroquine (HCQ) or chloroquine (CQ) and systemic glucocorticoids (GCs), both correlated with a possible risk of visual impairment [11-13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a retrospective analysis of uveitis etiology in 269 patients younger than 16 years old referred to an ophthalmological tertiary center found only one case of lupus [20], and a recent review of studies on the prevalence of SLE in patients with uveitis [21] reported rates varying from 0.1 to 4.8%. A prospective study of patients presenting with uveitis at an ophthalmology reference center in São Paulo, Brazil, including 15.3% of patients younger than 18 years old, showed that SLE was identified as the cause of uveitis in 14 out of 1053 (1.33%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature has shown that the prevalence of lupus is 0.47% in patients with uveitis and the PPV of antinuclear antibodies for the diagnosis is <3% [106]. Other studies have confirmed that immunologic investigations are rarely useful for the etiologic diagnosis of uveitis [83,84].…”
Section: Immunologic Investigationsmentioning
confidence: 99%